2014
DOI: 10.1007/s40261-014-0248-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Properties of Two Erlotinib 150 mg Formulations with a Genetic Effect Evaluation in Healthy Korean Subjects

Abstract: This study suggests that the test and reference formulations of 150 mg erlotinib have similar pharmacokinetic characteristics. Both had no major safety issues and were well-tolerated. The test formulation met the regulatory criteria for assuming bioequivalence to the reference formulation for both AUCt and C max. The additional genetic analysis demonstrated that the major metabolic enzymes of erlotinib did not significantly affect erlotinib metabolism, with the exception of CYP1A2*1M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Phenotyping studies assessing the effect of CYP3A4 variants on erlotinib metabolism were inconclusive and pre-emptive testing is not currently recommended. A PK study in a Korean population showed no difference in AUC exposure and C max of erlotinib in patients with CYP3A4 polymorphisms [206]. In a similar study, a polymorphism in CYP1A2*1 M resulted in a higher C max .…”
Section: Polymorphisms In Cyp3a4mentioning
confidence: 91%
See 1 more Smart Citation
“…Phenotyping studies assessing the effect of CYP3A4 variants on erlotinib metabolism were inconclusive and pre-emptive testing is not currently recommended. A PK study in a Korean population showed no difference in AUC exposure and C max of erlotinib in patients with CYP3A4 polymorphisms [206]. In a similar study, a polymorphism in CYP1A2*1 M resulted in a higher C max .…”
Section: Polymorphisms In Cyp3a4mentioning
confidence: 91%
“…Another contributing factor could be auto-induction of CYP3A4 by erlotinib. CYP450 induction often occurs on a transcriptional level and takes up to 2 weeks for increased expression, which may be missed in studies that do not assess steady state erlotinib levels [206,207]. There are limited studies evaluating the impact of CYP3A4 SNPs and gefitinib, osimertinib, and mobocertinib metabolism.…”
Section: Polymorphisms In Cyp3a4mentioning
confidence: 99%
“…In lung cancer patients, the CYP1A2*1M variant has been associated with higher maximum plasma concentration values after the intake of 150 mg of erlotinib, suggesting reduced enzyme activity. The impact on drug efficacy and toxicity is so far unknown [11]. …”
Section: Cytochrome P450 (Cyp)-mediated Phase I-metabolizing Enzymesmentioning
confidence: 99%
“…Blood samples were collected before dosing and 0.5, 1, 1.5, 2, 2.5, 3, 4, 6, 8, 12, 24, 48, 72 and 96 hours after oral administration. [7] These blood sample collecting times, including the dosing time, are set in the schedule table located on the left side. All scheduled times, calculated from the schedule table, are shown in the columns of scheduled time table on the right side.…”
Section: Application To Clinical Trialsmentioning
confidence: 99%